Effect of Ta content on formation mechanism of passivation film and corrosion resistance in ZrTiNbAl-system alloy - LI Shuwen; ZHANG Yang; MA Yaxi; DAI Pengfei; ZHANG Zhongwu (Cailiao gongcheng, 2024)
The formation mechanism of passivation film and corrosion resistance of (40-x)Zr-30Ti-20Nb-10Al-xTa (x=0, 2, 4, atom fraction/%, the same below, referred to as Tax alloy) high entropy alloy in a 0.3mol/L LiOH solution were investigated by potentiodynamic polarization, electrochemical impedance technique, Mott-Schottky analysis and potentiostatic polarization. The results show that the addition of appropriate amount of Ta (2%) helps to form a compact oxide film, which improves the corrosion resistance, while the excessive amount of Ta (4%) decreases the corrosion resistance due to the increase of oxygen vacancy concentration. The corrosion current density of the Ta2 alloy is 49.66 nA/cm2, which is less than the Ta0 and Ta4 alloys of 201.40, 70.16 nA/cm2. The concentration of oxygen vacancy point defect in the passivation film of the Ta2 alloy is 9.79×1018 cm-3, which is less than 2.13×1019, 2.05×1019 cm-3 in the Ta0 and Ta4 alloys, with the most compact passive film structure. The passivation film of the alloy is a stable n-type composed of ZrO2, Nb2O5, TiO2, Al2O3 and Ta2O5. Among them, the oxide content of ZrO2, Nb2O5 and TiO2 in the oxide film of the Ta2 alloy is the highest, which delays the dissolution rate of the primary oxide film and protects the matrix from further dissolution, with the best corrosion resistance.